Exploration of types of ventilated air chambers to improve thermal efficiency of bricks in fired clay (2020)
The products and construction systems for facades regulate energy transfer in the architectural envelopes. Therefore, this paper developed an exploration of types of ventilated air chambers to improve thermal efficiency of brick for masonry walls in fired clay, taking into account their role in buildings. The methodology involves three fundamental stages: design, simulation and analysis of results. The design stage proposes 3 brick typologies with ventilated air chamber. The second stage simulates the behavior of the heat transfer and heat fluxes of the models in extreme climatic conditions of San Jose de Cucuta, Colombia, in September in Ansys software through the finite element method. Finally, the analysis of results studies the relationship between the incorporation of the ventilated chamber, shape of the product and heat transfer of proposed models, in comparison with the multi-perforated brick. The results indicate that thermal benefit varies between 2.52 °C and 3.64 °C in the interior surfaces of proposed bricks. Moreover, incorporation of ventilated air chamber mitigates heat transfer and reduces energy concentration in the interior sides of new bricks design. In conclusion, innovation in brick design proves that new forms proposition generates added values such as thermal benefits related to comfort. This aspect is important to consider because it establishes a transformative perspective for brick industry through an innovative market that is committed to sustainability of architectural envelopes in order to reduce energy consumption of buildings.